HUBUNGAN MOTIVASI MENJADI PERAWAT DENGAN PRESTASI BELAJAR MAHASISWA FAKULTAS KEPERAWATAN TINGKAT DUA DI SALAH SATU UNIVERSITAS SWASTA INDONESIA [THE CORRELATION BETWEEN MOTIVATION TO PURSUE A NURSING CAREER AND THE LEARNING ACHIEVEMENT OF SECOND-YEAR NURSING STUDENTS AT A PRIVATE UNIVERSITY IN INDONESIA] - Paula, Veronica; Barus, Novita Susilawati; Naibaho, Juliati; Ortu, Juniarti; Mbolik, Mafalda (Nursing Current: Jurnal Keperawatan, 2024)
Becoming a nursing student requires strong motivation to ensure maximum learning outcomes, as the nursing profession involves managing disease conditions and dealing with people's lives.  Maximum learning achievement reflects a competent nurse who has the ability to meet patient needs and provide high-quality, satisfactory health services. Motivation encourages students to achieve their goals, and one impact of motivation on nursing students is that the higher the motivation to become a nurse, the greater the achievement they will attain. The purpose of this study was to find out the relationship between the motivation to become a nurse and the learning performance of a student of a nursing faculty in a private University in Indonesia. The data collection technique is total sampling with a sample of 295 respondents.  The research instrument used a motivation questionnaire to become a nurse and a learning achievement questionnaire. Data were analyzed using univariate and bivariate assays with the Spearman rho correlation test. The results showed that there was no relationship between motivation to become a nurse and learning achievement (p-value: 0,091) with the value of the correlation coefficient -.0.099. Researchers can then look at other factors that affect learning performance such as interests, talents, memory, physical condition, gender, learning process, environment, support from loved ones, and others.BAHASA INDONESIA Menjadi mahasiswa perawat perlu memiliki motivasi yang tinggi untuk menjadi seorang perawat guna mencapai prestasi belajar yang maksimal, mengingat profesi keperawatan ialah profesi yang menyangkut kondisi penyakit bahkan nyawa seseorang. Prestasi belajar yang maksimal mencerminkan perawat yang berkompeten yang mempunyai kemampuan dalam memenuhi kebutuhan pasien serta memberikan pelayanan kesehatan yang memuaskan dan berkualitas. Motivasi sendiri akan mendorong mahasiswa dalam mencapai suatu tujuan yang ingin dicapai, salah satu dampak motivasi pada mahasiswa keperawatan adalah semakin tinggi motivasi menjadi perawat semakin tinggi prestasi yang akan diraih. Penelitian ini bertujuan untuk mengetahui hubungan motivasi menjadi perawat dengan prestasi belajar mahasiswa fakultas keperawatan di salah satu universitas bagian barat. Teknik pengumpulan data adalah total sampling dengan instrumen penelitian yaitu angket motivasi untuk menjadi perawat dan angket prestasi belajar. Data dianalisis menggunakan uji univariat dan bivariat dengan uji korelasi rho Spearman.Hasil penelitian diperoleh bahwa tidak ada hubungan antara motivasi menjadi perawat dengan prestasi belajar (nilai-p: 0,091). Peneliti selanjutnya dapat melihat faktor-faktor lain yang mempengaruhi kinerja belajar seperti minat, bakat, memori, kondisi fisik, jenis kelamin, proses belajar, lingkungan, dukungan dari orang yang dicintai, dan lain-lain.